Are progressive chief prosecutors effective in reducing prison use and cumulative racial/ethnic disadvantage?: evidence from Florida - Mitchell, Ojmarrh (Criminology & public policy, 2022)
Research Summary Progressive chief prosecutors, campaigning on platforms calling for reducing prison populations and racial/ethnic disparities, have been elected in numerous jurisdictions across the United States in recent years. Yet, there is no empirical research that compares case outcomes between jurisdictions headed by progressive and traditional chief prosecutors. In this research, we utilize a cumulative case outcome approach that tracks cases from arrest to disposition to examine whether cases prosecuted under progressive chief prosecutors receive less punitive sanctions and exhibit smaller racial/ethnic disparities. We find that cases adjudicated in progressive jurisdictions are more likely to end without a felony conviction and less likely to result in a prison sentence. Racial but not generally ethnic disadvantage is evident in case outcomes, and racial disparities are smaller in jurisdictions led by progressive chief prosecutors. Policy Implications The election of progressive prosecutors is a radical departure from earlier approaches aimed at controlling prison populations and mitigating racial disparities. Instead of restricting the discretion of criminal justice actors, voters are relying on progressive, reformist prosecutors to use their enormous discretion in less punitive and more egalitarian fashions. This research indicates that progressive chief prosecutors do, in fact, reduce prison use and racial disparities.